() miR-182 is largely dispensable for adaptive immunity: lack of correlation between expression and function - Pucella, Joseph N. (J Immunol, 2015)
MicroRNA (miR)-mediated regulation of protein abundance is a pervasive mechanism of directing cellular processes. The well-studied and abundant miR-182 has previously been implicated in many aspects of T cell function, DNA repair and cancer. Here, we show that miR-182 is the most highly induced miR in B cells undergoing class switch recombination (CSR). To elucidate the requirement of miR-182 in lymphocyte function, we extensively characterized mice with a targeted deletion of Mir182. We show that despite its dramatic induction, loss of miR-182 has minimal impact on B cell development, the ability of B cells to undergo CSR ex vivo and to undergo antigen-driven affinity maturation in vivo. Furthermore, in striking contrast to knockdown studies that demonstrated the requirement of miR-182 in T cell function, miR-182 deficient mice display no defect in T cell development and activation. Finally, we show that T cell dependent immune response to experimental Listeria monocytogenes infection is intact in miR-182 deficient mice. We conclude that, contrary to previous studies, miR-182 does not play a significant role in all measured aspects of mouse adaptive immunity. This striking absence of a phenotype highlights the lack of correlation between expression pattern and functional requirement, underscores the limitations of using knockdown approaches to assess miR requirements, and suggests that miR networks may compensate for the chronic loss of specific miRs.